Estimating the indirect costs associated with the expected number of cancer cases in Mexico by 2020 - Cristina Gutiérrez-Delgado; Daniel Armas-Texta; Nancy Reynoso-Noverón; Abelardo Meneses-García; Alejandro Mohar-Betancourt (Instituto Nacional de Salud Pública, 2016)
Objective. To estimate the indirect costs generated by adults with cancer in Mexico from 2002-2020. Materials and methods. Using information from national sources and the national cancer incidence from GLOBOCAN, we estimated income lost due to premature death (ILPD), short-term benefits (STBs), disability pensions (DPs), and opportunity costs for the carer (OCCs) generated by patients with cancer. Amounts were reported in Mexican pesos. Results. We estimated 23 359 deaths and 216 679 new cases of cancer by 2020, which would be associated with a total indirect cost of 20.15 billion Mexican pesos. Men are expected to generate 54.9% of these costs. ILPD is expected to comprise the highest percentage of the cost (60%), followed by OCCs (22%), STBs (17%) and DPs (1%). Conclusions. From an economic perspective, the results emphasize the need to strengthen preventive interventions and early detection of cancer among adults to reduce its effect on the productivity of Mexico. DOI: http://dx.doi.org/10.21149/spm.v58i2.7792